Performance evaluation of concrete containing high volume palm oil fuel ash exposed to elevated temperature - Abdul Awal, A.S.M.; Shehu, I.A. (Elsevier, 2015)
The properties of concrete exposed to elevated temperature are of great importance in terms of structural stability and assessment of serviceability state of the structure. This paper presents the results of a study on the performance behaviour of concrete containing high volume palm oil fuel ash exposed to high temperature. Concrete samples were made where ordinary Portland cement was replaced by 50%, 60% and 70% palm oil fuel ash. The samples were thermally treated to elevated temperatures of 200, 400, 600 and 800 C in an electric furnace for a period of 1 h after attaining the peak temperature. Specimens exposed to elevated temperature were cured in air and were tested for visual observation, change in weight, ultrasonic pulse velocity and residual compressive strength. It has been observed that higher the temperature, higher was the residual weight loss of concrete samples. Along with the loss of residual compressive strength, the ultrasonic pulse velocity of concrete was also reduced at elevated temperature. Data generated in this study was used to develop simple relationship for expressing residual compressive strength as a function of ultrasonic pulse velocity.